2020
DOI: 10.1186/s40478-020-01023-3
|View full text |Cite
|
Sign up to set email alerts
|

BRAF V600E mutation mediates FDG-methionine uptake mismatch in polymorphous low-grade neuroepithelial tumor of the young

Abstract: We present a case of a 14-year old boy with tumor-associated refractory epilepsy. Positron emission tomography imaging demonstrated a region with heterogeneous high 11C-methionine uptake and a region with homogenous low 18F-fluorodeoxyglucose uptake within the tumor. Histopathological and genomic analyses confirmed the tumor as BRAF V600E-mutated polymorphous low-grade neuroepithelial tumor of the young (PLNTY). Within the high-methionine-uptake region, we observed increased protein levels of L-type amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
(49 reference statements)
2
15
0
Order By: Relevance
“…The unusual age of onset of the present case led us to critically perform a literature review and we found that, since its first description,[ 18 ] few cases of PLNTY have been reported in the English literature, mostly in the form of single case or small case series,[ 6 , 8 , 12 , 14 , 15 , 19 , 21 , 26 , 28 , 30 ] and almost all cases have been described in children and young adults;[ 6 , 8 , 12 , 14 , 15 , 19 , 21 , 28 , 30 ] the main findings of the literature review are summarized in [ Table 1 ]. Apart from the present case, to the best of our knowledge, only one case has been documented in a middle-aged adult patient by Riva et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The unusual age of onset of the present case led us to critically perform a literature review and we found that, since its first description,[ 18 ] few cases of PLNTY have been reported in the English literature, mostly in the form of single case or small case series,[ 6 , 8 , 12 , 14 , 15 , 19 , 21 , 26 , 28 , 30 ] and almost all cases have been described in children and young adults;[ 6 , 8 , 12 , 14 , 15 , 19 , 21 , 28 , 30 ] the main findings of the literature review are summarized in [ Table 1 ]. Apart from the present case, to the best of our knowledge, only one case has been documented in a middle-aged adult patient by Riva et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] The term “polymorphous low-grade neuroepithelial tumor of the young (PLNTY)” indicates a recently introduced epileptogenic neoplasm, first described in 2017 by Huse et al .,[ 18 ] affecting children and young adults and almost invariably characterized by oligodendroglioma-like histological appearance, diffuse cluster of differentiation-34 (CD34) immunohistochemical expression, and MAP kinase pathway-related molecular aberrations. [ 18 ] Since then, few other cases of PLNTY have been reported in the literature,[ 6 , 8 , 12 , 14 , 15 , 19 , 21 , 26 , 28 , 30 ] all in the form of single case reports or short case series, and most of them included children or young adults. [ 6 , 8 , 12 , 14 , 15 , 19 , 21 , 28 , 30 ] The temporal lobe is the most frequently affected site and epilepsy is the most common presenting symptom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, tSNE dimensionality reduction and unsupervised hierarchical clustering of three histologically defined cases of PLNTY with BRAF p.V600E mutation presented overall epigenetic similarity to FGFR2‐fused low‐grade neuroepithelial tumors but resolved into a separate methylation subgroup, implying that PLNTY may be composed of at least two distinct epigenetic subgroups, those with FGFR2 fusion and those with BRAF p.V600E mutation 87 . BRAF p.V600E‐mutated PLNTY cells were relatively vulnerable to dabrafenib and trametinib, advocating that a strategic targeted molecular therapy for the MAPK pathway may be particularly useful in surgically unresectable tumors 88 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the images are sure to be interpreted by specialists engaged in visualization of the structural 93 № 3 (13) 2022 ЛУЧЕВАЯ ДИАГНОСТИКА И ТЕРАПИЯ In patient Kh., a hyperperfusion site was also found in the structure of an epileptogenic substrate of unclear etiology, but according to ASL data it became possible to suspect the presence of neoplasm at the preoperative stage. These results worth further studying, especially in the light of a single mention of the atypical characteristics of PLNTY when using PET CT with 11 C-methionine and 18 F-fluorodeoxyglucose [13, p. 5-6].…”
Section: Discussionmentioning
confidence: 99%